Urgensi Diplomasi Ekonomi Sebagai Upaya Penyelesaian Sengketa Investasi Asing - Chidayatullah, Azizi (Journal of Economic and Business Law Review, 2023)
Single capital investment is an activity aimed at increasing economic growth and optimizing existing resources in Indonesia. However, in the implementation of foreign investment, there may be setbacks between foreign investors and the government. Article 32 paragraph (1) UUPM states that in the event of a transfer of capital between the investing government and the government, the parties must first complete the settlement through deliberation and consensus. Furthermore, Article 32 paragraph (2) UUPM states, in the event that the settlement as intended in paragraph (1) is not achieved, the dispute can be resolved through arbitration or alternative settlement or court in accordance with statutory provisions. However, in practice, arbitration settlements are detrimental to the Indonesian government, so that economic diplomacy can be an effort that needs to be prioritized for the sake of national interests. The research was carried out using normative juridical methods and aims to determine the urgency and positive impact of implementing economic diplomacy as an effort to resolve foreign investment. Keywords: Dispute Settlement , Economic Diplomacy, Foreign Investment,